Transmission of environmental knowledge and land skills in adaptation to climate change in the Arctic - Pearce, T; Notaina, R; Kudlak, A; Wright, Harold; Ford, J; Furgal, C; Smit, B (ArcticNet Inc., 2010)
This paper investigates the relationship between the transmission of environmental knowledge and land skills, and human adaptation to climate change. This relationship is empirically tested in an arctic community to document how environmental knowledge and land skills are transmitted among Inuit and what role, if any, do environmental knowledge and land skills play in adaptation to climate change.